Hazardous waste management : - LaGrega, Michael D. (McGraw-Hill, 2001)
Updated methods of waste disposal emphasizing site remediation and pollution prevention. Includes a comprehensive treatment of how toxic compounds move in the environment, including ground water and air modeling. Applicable to corporate management